Efektivitas Kelas Parenting Dalam Program Puspaga Terhadap Masyarakat di Balai RW 4 Kelurahan Tambak Wedi, Surabaya - Ismi Erli Syephiana; M Kendry Widiyatno (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
There are still many parents who apply parenting patterns by using violence against children such as hitting with a belt, broom, or other tools aimed at disciplining children. Therefore, it is necessary for the government to play a role in educating parents on how to care for children properly and certainly not using violence against children. Dinas Pemberdayaan Perempuan dan Perlindungan Anak Serta Pengendalian Penduduk Dan Keluarga Berencana DP3APPKB of Surabaya city provides parenting classes in the Puspaga Balai RW program aimed at education related to parenting patterns. Therefore, the researcher focuses on the effectiveness of parenting classes in the Puspaga program for the community at Balai RW 4 Tambak Wedi Village, Surabaya, which aims to determine the effectiveness of parenting classes that are held regularly for the Tambak Wedi community and to find out the supporting and inhibiting factors in the implementation of parenting classes. This research uses descriptive qualitative research supported by primary data and secondary data. Data collection techniques with interviews and observations that prove validity by making observations in the field. The results showed that the sustainability of parenting classes runs effectively and well because it is in accordance with what is to be achieved. Inhibiting factors can be from the community and the implementation of material that is difficult to do. The supporting factor is a clear legal basis so that it can be a reference material in implementing the program.